How Instructors Make a Difference: Panel Data Estimates from Principles of Economics Courses - Watts, Michael; Bosshardt, William (The Review of Economics and Statistics, 1991)
Differences in student learning associated with different instructors in three types of principles of economics courses are estimated using a fixed- and random-effects specification for an educational production function. Results show a wide variance in these instructor effects and that this variance increases directly with the amount of latitude instructors are given in the classroom. Copyright 1991 by MIT Press.